The Relationship between Digital Empathy and Bystander Behavior in Youth in Kupang City - Babys, Yustus D.P.S (Journal of Health and Behavioral Science, 2023)
Abstract. Communication in social media among teenagers is often found to be a process ofcyberbullying and the emergence of bystander behavior . Bystander behavior is divided into threeaspects, namely; passive Outsider , Defender of the cybervictim , and Reinforcer of the cyberbully .These three aspects can appear in someone depending on their digital empathy when theyencounter a cyberbullying process . The aim of this study was to determine the relationshipbetween digital empathy and bystander behavior ( passive outsider , defender of the cybervictim ,and reinforcer of the cyberbully ) in young people in Kupang City. The respondents in thisstudy were 374 young people from Kupang City, who used social media in theircommunication and were aged between 18-24 years. This study uses correlation analysis.The results showed that there was a coefficient relationship between digital empathy andbystander behavior ( Defender of the cybervictim ) of 0.230 and a significant value of p = 0.001 (p> 0.001).